Brain vein disorders in newborn infants. (12th September 2014) - Raets, Marlou; Dudink, Jeroen; Raybaud, Charles; Ramenghi, Luca; Lequin, Maarten; Govaert, Paul
<x xml:space="preserve">Abstract</x> The brain veins of infants are in a complex phase of remodelling in the perinatal period. Magnetic resonance venography and susceptibility‐weighted imaging, together with high‐resolution Doppler ultrasound, have provided new tools to aid study of venous developmental anatomy and disease. This review aims to provide a comprehensive background of vein development and perinatal venous lesions in preterm and term‐born infants, and to encourage further research in both the fetus and the newborn infant, with the aim of preventing or mitigating parenchymal injury related to diseases involving veins.